Uncovering viral RNA–host cell interactions on a proteome-wide scale. Issue 1 (January 2022) - Iselin, Louisa; Palmalux, Natasha; Kamel, Wael; Simmonds, Peter; Mohammed, Shabaz; Castello, Alfredo
Abstract : RNA viruses interact with a wide range of cellular RNA-binding proteins (RBPs) during their life cycle. The prevalence of these host–virus interactions has been highlighted by new methods that elucidate the composition of viral ribonucleoproteins (vRNPs). Applied to 11 viruses so far, these approaches have revealed hundreds of cellular RBPs that interact with viral (v)RNA in infected cells. However, consistency across methods is limited, raising questions about methodological considerations when designing and interpreting these studies. Here, we discuss these caveats and, through comparing available vRNA interactomes, describe RBPs that are consistently identified as vRNP components and outline their potential roles in infection. In summary, these novel approaches have uncovered a new universe of host–virus interactions holding great therapeutic potential. Highlights: RNA viruses interact with many RNA-binding proteins (RBPs) over the course of their life cycle in both pro- and antiviral capacities. The true extent of viral (v)RNA–host RBP interactions has only recently become clear as a result of developments in mass spectrometry and methods for specifically studying RBPs. There are now several methods available for directly studying the vRNA interactome; these use different approaches to specifically capture proteins interacting with vRNA and often yield very different results. When well designed and correctly interpreted, these methods have the potential to greatly enhance our understanding of viral infection by providing an unbiased insight into viral ribonucleoprotein composition. Proteins identified in the vRNA interactomes of multiple viruses might have panviral regulatory roles and could be promising targets for developing broad-spectrum antiviral therapies.